White Matter Hyperintensities and Their Impact in Brain Structure and Function in Alzheimer’S Disease and Behavioral Variant Frontotemporal Dementia Across Latin America and the United States: A Cross-Sectional Study - Garcia-Serrano, A (BioMed Central Ltd, 2025)
Background: White matter hyperintensities (WMHs) are a core manifestation of normal and pathological aging and are potentially linked to geographical differences in social and physical exposomes. Previous studies have not examined the impact of WMHs burden on neurodegeneration and cognition in healthy controls (HCs) and patients with Alzheimer’s disease (AD) and behavioral variant frontotemporal dementia (bvFTD) across geographic regions. This study addressed this gap by assessing the impact of WMHs burden on participants with and without dementia from Latin America (LA) and the United States (US). Methods: The study comprised 994 participants, including HCs (n = 402), AD (n = 359), and bvFTD subjects (n = 233) from LA and the US. WMHs and their association with grey matter (GM) atrophy, assessed through GM volume and cortical thickness, were evaluated and compared among groups (HCs, AD, and bvFTD) in LA and the US using a voxel-wise brain imaging approach (p < 0.05 family-wise error-corrected for multiple comparisons, minimum cluster size = 50 voxels). Multiple regressions analysis were employed to examine geographic differences in WMHs burden, WMHs-GM associations, and the effect of WMHs on cognitive performance, as assessed by the Mini-Mental State examination. Results: In the LA cohort only, higher WMHs load was associated with greater GM atrophy across all groups (HCs, AD, bvFTD), with a specific neurodegenerative pattern involving orbitofrontal, cingulate, and temporal areas. HCs from LA showed a greater WMHs load than their US counterparts, and this effect was dependent on GM atrophy. Finally, WMHs burden negatively impacted cognitive performance in dementia subjects, with a greater effect observed in bvFTD subjects from the US. Conclusion: WMHs have a more pronounced impact on neurodegeneration across the LA cohort, with a worse impact on HCs, which also show higher WMHs burden than their US counterparts. This could increase the risk of developing dementia. Moreover, WMHs burden differentially impacts cognition, with a greater negative effect observed in bvFTD subjects from the US. These findings highlight geographic variations in WMHs-related conditions, offering valuable insights for tailored future research. © The Author(s) 2025.